Does Auditor Quality and Tenure Matter to Investors? Evidence from the Bond Market - MANSI, SATTAR A.; MAXWELL, WILLIAM F.; MILLER, DARIUS P. (Journal of Accounting Research, 2004)
ABSTRACT We examine the relation between auditor characteristics (quality and tenure) and the cost of debt financing. Consistent with the hypothesis that audit characteristics are important to the capital markets, we find that (1) auditor quality and tenure are negatively and significantly related to the cost of debt financing, (2) the relation between auditor characteristics and the cost of debt is most pronounced in firms with debt that is noninvestment grade, and (3) both the insurance and information role of audits are economically significant to the cost of debt. Overall, our results suggest that, through their dual roles of providing information and insurance, auditor quality and tenure matter to capital market participants.